Multi-layer hybrid wired-cum-wireless sensor network design. (1st January 2012) - Maleki, Sima; Sepehri, Mohammad Mehdi; Farvaresh, Hamid; Nayebi, Abbas; Sawhney, Rapinder
Sensor networks with sensing, data processing and communicating capabilities have a broad spectrum of applications. Based on application requirements, various network configurations can be designed. One such robust configuration is a hybrid wired-cum-wireless sensor network that is composed of a wireless sensor network and a wired backbone which are inter-connected via access points. In this paper, the joint problem of configuring a hybrid wired-cum-wireless sensor network, position-constrained cluster head and access point placement is proposed. The design considers real wireless communication limitations, optimum locations of access points and cluster heads, and hybrid transmission structure of the network with the objective of minimising the network configuration cost. The problem is formulated as a mixed integer linear programming and solved using 'CPLEX'. Numerical results show that hybrid configuration is more cost effective than the wireless networks and leads to a longer lifetime at the expense of a more complex design.